Kenal saja tidak cukup: Eksplorasi Motif dan Bentuk Pertemanan Urban - Egi Prawita; Arka Nareswari; Maria Theresia Asti Wulandari; F Nurdiyanto (Jurnal Sains Psikologi, 2020)
Friendship is a form of social interaction which elicits positive affect, happiness, and promote mental health. Commonly, friendship is based on homophily. However, similarity often less seen in a diverse context, specifically urban area. Numerous interactions between migrants and nonmigrants will create a distinctive pattern with non-diverse area. The aim of this study is to frame friendship as perceived by urban youth in Yogyakarta with following questions: 1) what makes urban youth befriend each other, and 2) what kind of friendship they have. Indigenous qualitative study is used as a methodological approach. Author interviewed eight urban youth as participants. The findings suggest that urban youth in Yogyakarta befriend each other based on similarity in communication style, the relationship elicit supportive climate, proximity, and needs fulfillment. These reasons changing overtime, proofed by the consideration on cost-benefit relationship. Urban youth in Yogyakarta have several types of friends, categorized by intimacy. Intimate friendships consist of ‘sharing’ friend and close friend, while acquaintances are friends, functional friend, friends bound by space, and demographic friends. Implications are discussed further on recommendation on migrant friendship.